Warm-Glow versus Cold-Prickle: The Effects of Positive and Negative Framing on Cooperation in Experiments - Andreoni, J. (Quarterly Journal of Economics, 1995)
Experiments on privately provided public goods generally find that subjects are far more cooperative than predicted, while experiments on oligopolies and the commons almost always obtain the Nash-equilibrium predictions, despite being very similar games. This paper examines whether this difference could be due to the fact that with public goods there is a positive externality, while with the others the externality is negative. The result of the experiments is that subjects are more willing to cooperate when the externality is positive, even though the potential outcomes are the same. This suggests a behavioral asymmetry between the warm-glow of doing something good and cold-prickle of doing something bad.